Asteraceae in the Caparaó National Park, Espírito Santo, Minas Gerais, Brazil: Basal Clades and Vernonieae Cass - Machado, Polla Renon Rodrigues (2023)
To continue the studies of flora in the Caparaó National Park, a hotspot remnant, the present dissertation aims to do a floristic inventory and a systematic treatment for important groups within Asteraceae in mountain habitats of the Atlantic Forest. The Basal Clades and Vernonieae are remarkably diverse in South America and have their diversity underestimated at high-altitude environment in the Atlantic Forest. Herbaria collections, field expedition and searches on online databases were our strategies to perform this research, resulting identification keys, descriptions, taxonomic comments, examined material, distribution and phenology data, and conservation status. In this way, 10 new records are documented here, expanding the last compiled list and contributing with the knowledge about the biogeography of species. A total of 43 species and nine genera were found from 240 specimens analyzed, with twenty-three species having a narrower distribution, being Mutisia lutzii and Critoniopsis bradeana endemic to the Caparaó. A gap regarding conservation status was observed, thirty species have not had their threat level mensured. However, the present dissertation has two chapters. The first one (Chapter I) contains our study about the Basal Clades in the park, and the second one (Chapter II) about Vernonieae.